Regrow or Repair: An Update on Potential Regenerative Therapies for the Kidney. Issue 1 (January 2022) - Little, Melissa H.; Humphreys, Benjamin D.
Abstract : Fifteen years ago, this journal published a review outlining future options for regenerating the kidney. At that time, stem cell populations were being identified in multiple tissues, the concept of stem cell recruitment to a site of injury was of great interest, and the possibility of postnatal renal stem cells was growing in momentum. Since that time, we have seen the advent of human induced pluripotent stem cells, substantial advances in our capacity to both sequence and edit the genome, global and spatial transcriptional analysis down to the single-cell level, and a pandemic that has challenged our delivery of health care to all. This article will look back over this period of time to see how our view of kidney development, disease, repair, and regeneration has changed and envision a future for kidney regeneration and repair over the next 15 years.